Holochain: Secure Optimal Routing & Dynamic Task Offloading for Defense Against Multiple Attacks in MEC Assisted MANET-IoT Networks - BASKARAN, HARIKRISHNAN; THANGAVELU, BALASUBRAMANIAN (INFOCOMP Journal of Computer Science, 2022)
MANET with Internet of Things (IoT) plays a vital role in processing of data, sensing of data, and acquiring of data. Many of the existing works exploits MANET-IoT, which provides better results however they limits with data integrity problem, scalability issues, and energy consumption that affects the reliability in communication. In this paper by leveraging the short comings faced by the exiting works, we propose HSec-Route (Holochain based Secure Routing) approach with secure and energy efficient capability achieving QoS constraints. Initially nodes in the mobile network are authenticated to Holochain based centralized TA which exploits improved BLISS algorithm to ensure the legitimacy of nodes by considering multiple attributes. The authenticated nodes are clustered to improve the connectivity between nodes using Enhanced Fuzzy C-Means (EFCM) algorithm by considering several metrics. Here, Cluster Head (CH) is selected to minimize the energy consumption. After clustering, the routing between Cluster Members (CMs) to CH is carried out by performing two stages namely trust management stage and optimal forwarder stage. In trust management stage, both the direct and indirect trust are evaluated for every nodes to confirm the forwarders legitimacy, the ranking of nodes is done by using Grey Absolute Decision Analysis (GADA) based on trust values. With the help of trusts values and other metrics the optimal forwarder is selected by using Improved Particle Swarm Optimization (IPSO). Finally the nodes integrity is ensured by En-route filtering and the dishonest nodes are pruned out. The simulation is carried out by NS-3.26 simulation tool and performances are compared with existing works in terms several validation metrics. The validation results show that our proposed work out performs well than the existing works.